Pemilihan Hotel Pada Kelurahan Oesapa Selatan Menggunakan Metode Weighted Product - yampi kaesmetan; Yesaya Laga Nawa (Jurnal Teknologi Terpadu, 2017)
Hotel is one of the supporting facilities of tourism in a city. The diversity of the hotel make tourists often faced difficulty in determining the choice of hotel that suits your needs and desired criteria. Through a computerized application, can help prioritize the selection of the hotel. The results of the election study with WP method can be used to perform perangkingan list of alternatives hotel in southern Oesapa village for visitors so that the hotel needs can be met based on the criteria of visitors. The output of this system in the form of priority Oesapa best hotel in the southern villages. With this application, people who want to stay at the hotel can be easier in choosing a hotel to suit the need. Keywords: Hotel, South Oesapa, Wighted Product.